Supervisi dalam Monitoring Tugas Pendamping di Family Development Session Program Keluarga Harapan - Siti Syahmira Aulia Noor; Sudarini (Institute of Social and Political Science Jakarta (Institut Ilmu Sosial dan Ilmu Politik Jakarta - IISIP Jakarta), 2022)
The Family Hope Program (PKH) is a program designed with the aim of improving people’s lives. One of the success of this program is determined by the intensive and sustainable program assistants who have roles as facilitators, educators and community representatives.The role of a supervisor in monitoring mentors of the PKH is essential to be studied. The supervisor supports and empowers mentors, especially in the Family Development Session (FDS) activity. This article describes the implementation of the PKH supervision function based on the results of research in the Cimanggis sub-district, Depok. The research method used is descriptive qualitative with primary and secondary data collection through observation, interviews and documentation. As a result, this research uncovers three roles of a supervisor in this program. First is an administrative function comprising making reports, case management, and conflict and complaint management. Another part is to educate and manage the value and knowledge transfer to the mentors. Lastly, the supervisor’s role in the program is to provide moral support and resources to mentors.